2020
DOI: 10.1002/jcp.30091
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA CircCDH13 contributes to the pathogenesis of osteoarthritis via CircCDH13/miR‐296‐3p/PTEN axis

Abstract: Circular RNAs (circRNAs) are involved in a variety of human diseases; however, the function of circRNAs in osteoarthritis (OA) remains largely unknown. In this study, we investigated the role of CircCDH13 in OA and its underlying mechanisms. CircRNA expression profiles in OA and normal cartilage tissues were detected by microarray. The expression pattern, functional role, and mechanisms of CircCDH13 in OA were studied in vitro and in vivo. Gain‐of‐function and loss‐of‐function approaches were used to demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Upregulated circCDH13 has been detected in OA chondrocytes and in HCs treated with IL-1b and TNF-a. 74 Knocking down circCDH13 downregulated MMP13 and ADAMTS5 and increased COL2A1 and aggrecan; all of these effects were reversed by the overexpression of circCDH13. circCDH13 can bind to miR-296-3p, acting as a sponge, and the downstream targets of circCDH13/miR-296-3p were investigated.…”
Section: Roles Of Circrnas In Apoptosismentioning
confidence: 95%
“…Upregulated circCDH13 has been detected in OA chondrocytes and in HCs treated with IL-1b and TNF-a. 74 Knocking down circCDH13 downregulated MMP13 and ADAMTS5 and increased COL2A1 and aggrecan; all of these effects were reversed by the overexpression of circCDH13. circCDH13 can bind to miR-296-3p, acting as a sponge, and the downstream targets of circCDH13/miR-296-3p were investigated.…”
Section: Roles Of Circrnas In Apoptosismentioning
confidence: 95%
“…During previous study, some researchers identified the corresponding conservative sequences of circRNA between human and mouse and then used animal sequences to complete animal experiments instead of human. 58 However, a large number of circRNA do not exist conservative sequences in other species. In our study, the principium of in vivo experiments was to rely on the injected overexpressed human circSLC7A2 virus to bind to miR-4498 in mice, which in turn affected the expression of TIMP3 in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of CircCDH13: chondrocyte apoptosis↓, ECM catabolism↓, anabolism↑, in vivo: alleviated OA. [ 234 ] Abbreviations: ASC, adipose tissue-derived mesenchymal stromal cells; FUT, Fucosyltransferase; HMGB1, High mobility group box 1; i.a., intraarticular; MAPK, MAP kinase; miR, microRNA; PARP, Poly(ADP-ribose)-Polymerase; TGFBR2, Transforming growth factor β receptor 2; Wnt, wingless and integration site-1. …”
Section: Genetic Regulators Of Inflammatory/catabolic Gene Expressionmentioning
confidence: 99%